Evaluación funcional y estructural del puente sobre el río Chibunga, ubicado en la Vía calpi-gatazo grande, parroquia Cajabamba, cantón Colta, provincia Chimborazo - Aguayo Aróstegui, Sofía Arianna (2017)
Functional and estructural evaluation of the bridge over the river Chibunga, located on the road Calpi-Gatazo grande, Cajabamba parish, Colta canton, Chimborazo province. ABSTRACT: The bridges are built to communicate places between which there is a river, channel or other obstacle that obstructs the communication. For this reason, bridges and roads must be optimal so that they will allows a perfect development of the country in the economic, technological and social areas. Ecuador does not have a system that allows an adequate administration of bridges after their construction which directly influences the useful life. Therefore, for the project "functional and structural evaluation of the bridge over the river Chibunga, located on the road Calpi-Gatazo grande, Cajabamba parish, Colta canton, Chimborazo province", the structural management system of bridges of Costa Rica, the guide of inspection of bridges of Peru and the guide of functional and structural inspection of bridges of reinforced concrete type slab and slab on beams of Ortiz and Sánchez were used. This compilation of manuals and guides was adapted according to the bridge conditions. The evaluation process was divided into five areas: superstructure, infrastructure, accessories, complementary works and river flow. Element by element, the pathologies and their weighting were detailed resulting in the final grade of 9 and the state of the bridge was defined as very poor. As a solution to the problem, it is proposed the redesign of the bridge based on the aashto normative and coupling it in the most optimal way with its access routes, consequently the well-being and safety of its users will be guarantee